The Impact of Population Size, Unemployment Rates, and the Minimum Wage on Poverty in Indonesia: A Panel Data Analysis of 33 Provinces from 2015 to 2023 - Yureza Aprizani (Yayasan Rahmat Islamiyah, 2026)
Poverty is a socioeconomic issue that remains a key focus of development in Indonesia. Poverty rates are influenced by various factors, including population size, unemployment rates, and minimum wage policies. This study aims to analyze the impact of population size, unemployment rates, and minimum wages on poverty rates in Indonesia. The research method employed is a quantitative approach using panel data analysis covering 33 provinces in Indonesia over the 2015–2023 period. The data used are secondary data obtained from the Central Statistics Agency (BPS) and other relevant sources. The analysis techniques employed include the selection of panel data models (Common Effect Model, Fixed Effect Model, and Random Effect Model) as well as testing of classical assumptions. The results indicate that, simultaneously, population size, unemployment rates, and minimum wage policies have a significant impact on poverty rates in Indonesia. These findings indicate that population size, unemployment rates, and minimum wage policies are contributing factors to the high poverty rate in Indonesia. Therefore, the government is expected to formulate policies focused on controlling population growth, reducing unemployment rates, and improving workers’ welfare to sustainably reduce poverty levels.